2013
DOI: 10.1039/c3nr00760j
|View full text |Cite
|
Sign up to set email alerts
|

A high performance hybrid capacitor with Li2CoPO4F cathode and activated carbon anode

Abstract: For the first time, we report the possibility of utilizing Li2CoPO4F as a novel cathode material for hybrid capacitor applications. Li2CoPO4F powders were prepared by a conventional two-step solid state method. A hybrid cell was fabricated using Li2CoPO4F as the cathode along with activated carbon (AC) as the anode in 1 M LiPF6 dissolved in 1 : 1 EC/DMC electrolyte and its electrochemical properties were examined by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and constant current char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
2
59
1
Order By: Relevance
“…After fitting the impedance spectrum, the internal resistance value was found to be 0.8 . This value is smaller than those reported for non-aqueous Li-HSCs, 42,43 which may in part explain the advantage of aqueous electrolytes. The relationship between energy density (E) and power density (P) is shown in Fig.…”
Section: Resultscontrasting
confidence: 76%
“…After fitting the impedance spectrum, the internal resistance value was found to be 0.8 . This value is smaller than those reported for non-aqueous Li-HSCs, 42,43 which may in part explain the advantage of aqueous electrolytes. The relationship between energy density (E) and power density (P) is shown in Fig.…”
Section: Resultscontrasting
confidence: 76%
“…Thee mployed anode and cathode capacities are selected at ar elatively low current density because these values are close to their theoretical capacities.I nt he half-cell tests, the highest reversiblec apacities of 112a nd 150 mA hg À1 are afforded by the SNMG cathodea nd LTOa node, respectively.T hus, the mass loading ratio of the positive to negative electrodes is fixed at 1.12. Specifically,a value of 86.2 Wh kg À1 is obtained for the fabricated SNMG/LTO LIHC at ap owerd ensity of 532 Wkg À1 ,w hereas the AC/LTO LIHC only affords 62.8 Wh kg À1 under acomparable powerdensity.A lthough am onotonous decrease in energy density is observed with increasing power density,t he SNMG/LTO LIHC still maintains an energyd ensity of 24.8 Wh kg À1 at ar elatively high powerd ensity of 7443 Wkg À1 .I nc ontrast, the AC/LTO LIHC only retains an energy density of 11.6 Wh kg À1 at ap ower density of 6946Wkg À1 .I ti sw orth mentioning that the elec-trode behavior of the SNMG/LTO LIHC, with respectt oe nergy density,i sa lso significantly larger than those reported for ACbased LIHCs configured with otherl ithium intercalation electrodes,s uch as AC/C-LTO, [39] AC/TiO 2 -RGO, [40] AC/TiO 2 , [41] AC/ LiCrTiO 4 , [33] AC/graphene-wrapped LTO, [42] AC/Li 2 CoPO 4 , [43] AC/ LiMnBO 3 , [44] and AC/Nb 2 O 5 @graphene [45] LIHCs.T he SNMG/LTO LIHC delivers an initial capacitance of 128.6 Fg À1 and maintained about 111.9 Fg À1 after 2000 cycleswith acoulombic efficiency of about100 %atacurrent density of 1Ag À1 ;this corresponds to ac apacitance retentiono f8 7% (Figure 7c). Although the large potential window range is beneficial for the outputo fe nergy density,t he exorbitant charge potential (> 4.5 V) usually leads to the decomposition of electrolyte.…”
Section: Resultsmentioning
confidence: 81%
“…The better cyclic stability of the LMB‐NB anode in the half‐cell could be attributed to the presence of a porous carbon network between the LMB‐NB particles, which facilitate Li‐ion diffusion even at a high‐current C/DC process. Moreover, uniformly distributed LMB‐NB particles also improved the contact between the particle/particle and the particle/current collector, ensuring the improvement of electrical conductivity; hence lithium‐ion‐storage capability was enhanced 23. 30 On the other hand, the inherent conductivity and morphological features of PANI‐NBs aided its stable electrochemical performance 33.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the storage mechanism of the PANI‐NF/LMB‐NB cell was mostly based on the doping/undoping of the electrolyte active species (PF 6 − ) from the LiPF 6 electrolyte (PAN‐NF cathode), and the reversible phase transformation that occurred during the Li + intercalation reaction (LMB‐NB anode) 6. 22, 23 The shapes of the CV traces showed that capacitance behavior depended on scanning rate 21. 23, 27 Specific capacitances of approximately 100, 75, 67, 57, 54, and 50 F g −1 were achieved at scan rates of 2, 5, 10, 20, 30, and 50 mV s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation